2020
DOI: 10.1093/trstmh/traa155
|View full text |Cite
|
Sign up to set email alerts
|

Ethical dimensions of neglected tropical disease programming

Abstract: The global movement to control and eliminate neglected tropical diseases (NTDs) is grounded in an ethic of social justice, solidarity and health equity. NTD programmes deliver significant health benefits in socially complex environments characterized by poverty and economic disparity. We used two ethics frameworks—principlism and Upshur's public health framework—to examine ethical challenges faced by NTD programmes. They include management of serious adverse reactions associated with preventive chemotherapy, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 30 publications
2
8
0
Order By: Relevance
“…In line with Addiss et al ,20 we found that only a small number of publications specifically focus on the ethics of MDA. Instead, ethical issues often come up as side points in discussions or arise in qualitative interview studies with different primary aims.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In line with Addiss et al ,20 we found that only a small number of publications specifically focus on the ethics of MDA. Instead, ethical issues often come up as side points in discussions or arise in qualitative interview studies with different primary aims.…”
Section: Discussionsupporting
confidence: 89%
“…sustained commitment and vigilance are needed to detect and respond to recrudescence of infection and develop the infrastructure, such as sanitation, vector control and primary health services, needed to sustain public health gains 20…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As the results of our survey show, field epidemiologists are aware of these gaps, not only within the context of community-based implementation research, but more acutely, within public heath practice. For example, the emphasis on informed consent in the context of human subjects research does not always extend to public health practice, particularly for population-level interventions [ 17 ].…”
Section: Discussionmentioning
confidence: 99%